1999
DOI: 10.1590/s1413-294x1999000100006
|View full text |Cite
|
Sign up to set email alerts
|

Conversas sobre sexualidade na família e gravidez na adolescência: a percepção dos pais

Abstract: Resumo Estudou-se a percepção sobre dificuldades informativas e comunicativas em conversas sobre sexualidade com as filhas. Entrevistou-se quatro casais e cinco mães, envolvendo oito famílias com filhas adolescentes grávidas, pertencentes à classe média baixa. Na análise, seguiram-se os três passos reflexivos da Psicologia Fenomenológica: descrição, que indica o modo de compreensão do tema em foco; redução, que especifica criticamente o modo de compreensão e sua relação com a concretude da situação; e interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
26

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 3 publications
(4 reference statements)
0
8
0
26
Order By: Relevance
“…However, it has been unable to work on children's sexual education due to the difficulties parents report regarding sexual issues (1) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been unable to work on children's sexual education due to the difficulties parents report regarding sexual issues (1) .…”
Section: Introductionmentioning
confidence: 99%
“…
The family is considered a relevant social structure in the education of its children in growth and development, especially in terms of sexuality.However, it has been unable to work on children's sexual education due to the difficulties parents report regarding sexual issues (1) .Adolescents have had an intense share in the AIDS epidemic, and the number of cases is substantial among young people. Studies show that the adopted preventive practices basically consist in the distribution of preservatives, which is not fully efficient, and that further research on sexual and reproductive health of these people is needed (2) .

Over In terms of economic status, 11 (42.3%)

reported family income lower than one minimum wage; nine (34.6%) between one and two minimum wages; four (15.4%) reported three minimum wages and two (7.7 %) reported an income of four minimum wages.

Regarding the number of children, the study shows that 14 (53.8%) parents have one to two children; nine (34.6%) have three to four children, and three (11.6%) have five children.

…”
mentioning
confidence: 99%
“…It is observed that they can perceive adequately what happens to their daughters in terms of sexuality, however, they fail to offer effective sexual guidance because they overestimate the knowledge of their daughters in respect to contraceptive methods, either by trying to delay their initial sexual encounter, or because they feel inept to deal with these issues (3) .…”
Section: Discussionmentioning
confidence: 99%
“…This fact reveals a phenomenon often overlooked in the family environment, which is education about sexuality in adolescence (3) .…”
Section: Introductionmentioning
confidence: 94%
“…A informação dada aos jovens sobre a sexualidade é ambígua, pois os pais não têm clareza dos valores que pretendem transmitir aos filhos 21 . Esse descompasso entre aquilo que os pais falam e suas atitudes em relação à sexualidade de seus filhos e filhas, acaba por exigir uma revisão de seus padrões e atitudes relativos à sexualidade e mudanças para adaptar-se a normas mais liberais.…”
Section: +++ Fundação Do Sistema Estadual De Análise De Dados -Seade unclassified